Early Miocene shallow-water corals from La Guajira, Colombia: Part II, Mussidae–Siderastreidae and Milleporidae. (28th December 2018) - Flórez, Paola; Zapata-Ramírez, Paula; Klaus, James S.
Abstract: In this contribution we describe and illustrate 14 coral morphospecies collected from the early Miocene Siamaná (Aquitanian–Burdigalian) and Jimol (late Burdigalian) formations of the Cocinetas Basin in La Guajira Peninsula, northern Colombia. Eleven were identified as already established species including seven genera belonging to the families Mussidae, Pocilloporidae, Poritidae, Siderastreidae, and Milleporidae; the other three remain in open nomenclature. Nine of the 11 species identified (81%) are extinct. The remaining two living species, Siderastrea siderea and Millepora alcicornis, are common on modern Caribbean reefs. Their presence in the Siamaná Formation extends their temporal range in the Caribbean region to the early Miocene. Most of the taxa described here were hermatypic and zooxanthellate corals of the order Scleractinia, with the exception of the fire coral Millepora alcicornis, of the order Anthothecata, family Milleporidae. The coral fauna recorded in the Siamaná and Jimol formations is typical of shallow and calm waters of the Oligocene–Miocene transition.